Generating 'Creative Tourism Kampung' Through Collaborative Approach in Local Community (A case Study of Kampung Kreatif Dago Pojok) - Rahmany, Rizky; Djajadiningrat, Surna Tjahja (Journal of Business and Management, 2014)
Bandung, well-known as creative city in Indonesia, still has several unanswered questions regarding to its ability to solve poverty and fatuity. Where the expanse of urban area is growing faster within its dominant form of neoliberal urban development, there are some marginal areas sticking out that have lack of attention from government which creates a social jealousy, imbalance in prosperity and potential to a form of social conflict. While there are some unexplored potentials in marginal areas of the city or known as â€œkampung kotaâ€, a concept of creative tourism village or locally-known as â€œkampung wisata kreatifâ€ has been created to provide a place for local community to explore their creativity/potentials and to create a social movement in â€œkampungâ€ that contribute to the development of Bandung in becoming creative city. Dago Pojok is a sample of residential area for lower class in Bandung city that has been branded as â€œkampung kreatifâ€ since 2003 by Komunitas Taboo and has contributed to Bandung's tourism face for providing local wisdom and authentically traditional activity within its community. The vision of this movement is objected to ignite the soul of kampungs as part of city. By understanding and analyzing the case, this paper provides recommendation that hopefully can be helpful for actuators or implementer in field focus of social development & empowerment, social enterprise, creative industry, anthropology, urban peace development, art educational system, stakeholders engagement and other relevant fields.Keywords: Urbanization, Inequality, Creative Tourism Kampung, Dago Pojok,Community Empowerment,Stakeholders Engagement